Pengaruh Kualitas Auditing Laporan Keuangan terhadap Pengambilan Keputusan - Mahya Ulum Anjali; Viona Rahma Wardani; Viola Dhea Febrianti Ali Khan (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Lenders and investors use audit reports as part of their decision-making process. Research has revealed that auditing of financial statements has a positive impact on investors' decision making, which implies that a lack of proper auditing of financial statements will result in poor investment judgment. As a result, auditing financial reports must be detailed and comprehensive because users rely on these reports to make economic and financial decisions. This research concludes that auditing financial reports is certainly very valuable for users in making decisions, as evidenced by the impact on investment decisions and investor funding.